2018
DOI: 10.1016/j.pediatrneurol.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Concussion Influences the Number of Subsequent Concussions

Abstract: Individuals self-reporting a concussion at a young age sustained a higher number of concussions before age 18. Concussion prevention, recognition, and reporting strategies are of particular need at the youth level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The median age of first concussion in this sample of private high school student athletes was 9.5. A study conducted by Schmidt et al reported individuals who reported their first concussion during childhood (less than 10 years old) doubled the risk of sustaining a subsequent concussion compared to individuals who reported their first concussion during adolescence (10–18 years old). Due to an increased susceptibility for subsequent concussions, and often more severe outcomes after one has sustained an initial concussion, it is important that any youth with a suspected concussion be removed from play and evaluated by a health care provider and then follow return‐to‐learn and return‐to‐play protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of first concussion in this sample of private high school student athletes was 9.5. A study conducted by Schmidt et al reported individuals who reported their first concussion during childhood (less than 10 years old) doubled the risk of sustaining a subsequent concussion compared to individuals who reported their first concussion during adolescence (10–18 years old). Due to an increased susceptibility for subsequent concussions, and often more severe outcomes after one has sustained an initial concussion, it is important that any youth with a suspected concussion be removed from play and evaluated by a health care provider and then follow return‐to‐learn and return‐to‐play protocols.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not compare age of first concussion because of low sample sizes among our concussion cohorts. Schmidt and colleagues reported that participants self-reporting their first concussion during childhood had an increased risk of sustaining subsequent concussions (RR = 2.19) compared to participants self-reporting their first concussion during adolescence [39]. Future research should examine the association between age of first concussion and later-life outcomes.…”
Section: Afe < 10 Yearsmentioning
confidence: 99%
“…Health care providers often have to make difficult decisions regarding when an athlete is fit to safely return to sport/activity based on self-reporting of symptoms and their severity, and clinical testing. Self-reports, however, are highly subjective and also influenced by socio-cultural factors [70,71]. Moreover, emerging literature is showing that neurophysiological changes persist well after clinical recovery [15][16][17][18][19][20][21][22][23], suggesting that athletes may be returning to activity before their brains have fully recovered and may therefore be at increased risk of additional brain injury [66].…”
Section: Stage 3: Assessing Concnet's Performancementioning
confidence: 99%
“…Moreover, emerging literature is showing that neurophysiological changes persist well after clinical recovery [15][16][17][18][19][20][21][22][23], suggesting that athletes may be returning to activity before their brains have fully recovered and may therefore be at increased risk of additional brain injury [66]. In fact, a history of prior concussions is one of the strongest predictors of future concussions [71][72][73]. Specifically, high school athletes with prior concussions have >2× higher risk of suffering subsequent concussions [72,73] and with each successive injury, have a growing risk for sustaining long term neurological and mental health complications.…”
Section: Stage 3: Assessing Concnet's Performancementioning
confidence: 99%
See 1 more Smart Citation